Labour Taxation in Poland Compared to the Other OECD Countries - Kryńska, Elżbieta (Comparative Economic Research. Central and Eastern Europe, 2014)
The aim of the study is to identify the level and diversity of labour taxation, expressed by the so-called tax wedge, in Poland compared to the other OECD countries. The identification is based on an analysis of statistical data collected in the OECD database for the years 2000-2012. The study interprets key terms such as labour taxation, tax wedge, and non-wage costs of labour. The further section synthetically discusses theoretical findings and the results of empirical research concerning effects of labour taxation on the functioning of the labour market and, in particular, its impact on employment and unemployment. The author’s own research includes a comparative analysis of tax wedge sizes in different household types in Poland and the other OECD countries in the years 2000-2012. The major conclusion of the analysis is that labour taxation in Poland insufficiently takes into account the financial situation of low-earning individuals and those providing for children (i.e. children within households). The results of the conducted research form the basis for drawing synthetic conclusions and making recommendations for Poland. The main suggestion is that a selective reduction in the non-wage costs of labour of low-earning individuals and those burdened with family responsibilities should be considered.